Presenting ‘Lodho Ayam Kampung’ as Gastronomic Tourism Attraction in Trenggalek Regency, East Java Province of Indonesia - Palestho, Andrea Basworo (Gastronomy Tourism Journal, 2020)
Trenggalek Regency has a specialty cuisine called 'Lodho Ayam Kampung' whose existence has been inherited in the community so that it has its history. However, this is not considered as a gastronomic tourism attraction in Trenggalek Regency recently. Therefore, the objectives of this research are to present 'Lodho Ayam Kampung' as a gastronomic tourism attraction in Trenggalek Regency and to examine the gastronomic aspects that exist in the cuisine. This research uses descriptive qualitative research methods also data collecting method is using in-depth interview techniques. The results of this study conclude that 'Lodho Ayam Kampung' has historical and philosophical values that can be promoted as gastronomical tourism attractions.